Survival of the biological control agent Candida sake CPA‐1 on grapes under the influence of abiotic factors - Calvo Garrido, Carlos; Viñas, Inmaculada; Usall, Josep; Rodriguez Romera, Mariela Carmen; Ramos, María Concepción; Teixidó, Neus (Wiley, 2019)
Aims: As reliability of preharvest applications of biological control agents (BCAs) to control fruit pathogens is highly dependent on the survival of the selected organism, this study aimed to describe the population dynamics of the yeast‐BCA Candida sake (Saito & Ota) CPA‐1 on grape berries under the effect of abiotic factors such as temperature, relative humidity, sunlight and rainfall. Methods and Results: Candida sake (5 × 107 CFU ml−1), combined with different concentrations of the food additive Fungicover®, was applied on grape berry clusters. Treated clusters were then exposed to abiotic factors in field or laboratory conditions, recovering populations to describe C. sake population dynamics. The addition of Fungicover significantly increased C. sake multiplication under optimal growth conditions and improved survival under fluctuating abiotic factors. After field applications, significant differences in populations on grape bunches exposed or covered by fine foliage were detected. Simulated rainfall washed off C. sake populations by 0·6–0·9 log units after 20 mm of rain volume. Allowing populations to establish for 24 h or more, prior to a rain event, persistence on grape berries significantly increased and the effect of rain intensity was not observable. Conclusions: Candida sake demonstrated high survival ability under unfavourable environmental conditions and persistence under intense rain. The study evidenced the importance of the first period just after application for C. sake survival on grape tissues and also the protective effect of the additive Fungicover.